The first catalytic synthesis of an acrylate from CO2 and an alkene: a rational approach - Lejkowski, Michael L.; Lindner, Ronald; Kageyama, Takeharu; Bódizs, Gabriella Éva; Pleßow, Philipp; Rominger, Frank; Hofmann, Peter; Limbach, Michael (Chemistry - a European journal, 2012)
For more than three decades the catalytic synthesis of acrylates from the cheap and abundantly available C1 building block carbon dioxide and alkenes has been an unsolved problem in catalysis research, both in academia and industry. Herein, we describe a homogeneous catalyst based on nickel that permits the catalytic synthesis of the industrially highly relevant acrylate sodium acrylate from CO2, ethylene, and a base, as demonstrated, at this stage, by a turnover number of greater than 10 with respect to the metal.
Gesehen am 07.08.2018
Dedicated to Professor Dieter Seebach on the occasion of his 75th birthday